Social influence on route choice in a virtual reality tunnel fire - Kinateder, Max; Ronchi, Enrico ; 0000-0002-2789-6359; Gromer, Daniel; Müller, Mathias; Jost, Michael; Nehfischer, Markus; Mühlberger, Andreas; Pauli, Paul (Transportation Research. Part F: Traffic Psychology and Behaviour, 2014)
Introduction Evacuation from tunnel fire emergencies requires quick decision-making and swift action from the tunnel occupants. Social influence (SI) has been identified as an important factor in evacuation. Methods Two experimental groups were immersed into a virtual road tunnel fire. In the SI group participants saw a virtual agent moving on the shortest route to the nearest emergency exit. In the control group, participants were alone. Destination and exit choices were analyzed using functional analysis and inferential statistics. Results SI affected route choice during evacuation but not destination choice: There were no group differences regarding destination choice. Participants in the SI group were more likely to choose a route similar to the virtual agent. Participants in the control group were more likely to choose a longer route along the tunnel walls. Discussion Social influence does not only affect behavior activation but also more subtle choices, such as route choice, during evacuation.
Keywords: Fire evacuation; Social influence; Travel paths; Tunnel fire; Virtual reality; Functional analysis; Region of interest analysis